Internal Control System, Internal Audit, and Good Corporate Governance to Produce Quality Financial Reports in Banking Companies - Risnaningsih Risnaningsih; Yustina Elisabeth Elfrida (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2026)
Introduction/Main Objectives: The purpose of this study is to determine the influence of the internal control system, internal audit, and good corporate governance on the quality of financial statements in banking companies listed on the IDX partially and simultaneously. Methods: The research was conducted based on quantitative methods. The determination of this research sample uses the purposive sampling method so that a research sample of 8 banking companies registered on the IDX was obtained. The data of this study uses the financial statements of banking companies for the 2019-2023 period. The data analysis method used is multiple linear regression. Results/Findings: The results of the study prove that the internal control system has a significant effect on the quality of financial statements with t count = 4,726, internal audit has a significant effect on the quality of financial statements with t count = 3,970 and good corporate governance has a significant effect on the quality of financial statements with t count = 4,487. The results of the joint internal control system, internal audit, and good corporate governance have a significant effect on the quality of financial statements in banking companies listed on the IDX with a value of F count (13,605). Conclusions: The importance of quality financial reports lies in helping stakeholders in making economic decisions.